Preventive Maintenance as a Key to Reliable Power Distribution in Indonesia: Pemeliharaan Preventif sebagai Kunci untuk Distribusi Listrik yang Andal di Indonesia - Hariswanda, Yuswono; Anshory, Izza (Procedia of Engineering and Life Science, 2024)
This study investigates the frequent disturbances in a 20 kV Medium Voltage Overhead Line (SUTM) distribution network, identifying both internal channel issues and external disruptions such as natural events and wildlife interference as primary factors. The research evaluates the effectiveness of Right Of Way (ROW) maintenance, a preventive strategy involving tree trimming, pole realigning, and component replacement. Results demonstrate that ROW maintenance significantly boosts network reliability and effectiveness, suggesting that systematic preventive maintenance is crucial for improving power distribution resilience globally. Highlights: Swift disruption resolution: Prompt response is vital for network reliability. Internal and external factors: Disturbances arise from channel issues and external elements. Preventive maintenance: ROW approach enhances network efficiency, tackling various issues. Keywords: Distribution Network Disruption, ROW Maintenance, Medium Voltage Air Line Maintenance